COMPARATIVE STUDY OF EFFICIENCY AND PRODUCTIVITY BETWEEN CONVENTIONAL COMMERCIAL BANKS AND ISLAMIC COMMERCIAL BANKS: EVIDENCE FROM INDONESIA - Evania Herindar; Nadia Nurul Izza (Airlangga International Journal of Islamic Economics and Finance, 2022)
Abstract This study aims to analyze and compare the efficiency and productivity of Conventional Commercial Banks (BUK) and Islamic Commercial Banks (BUS) in Indonesia, with 19 BUK and 14 BUS in Indonesia. This study uses the CRS and VRS models in analyzing efficiency with Data Envelopment Analysis while analyzing productivity using the VRS model using the Malmquist Productivity Index. The results of this study indicate that there are still BUK and BUS bankers who have not achieved maximum efficiency, and there are still many of the two types of banks with low efficiency. The leading cause of the inefficiency of BUK and BUS in Indonesia is caused by output variables, namely the amount of financing and operating income. This study also revealed that the Covid-19 pandemic caused a decrease in the efficiency of the BUK, while the efficiency of the BUS was relatively stable and even slightly increased. Furthermore, based on an analysis of productivity during the Covid-19 pandemic, BUK and BUS in Indonesia experienced an increase due to high technological changes. Then this study also revealed the results of the Malmquist index score. Changes influence changes in productivity efficiency and changes in technology. This study finds that the dominant factor that causes the increase in productivity of BUK and BUS in Indonesia is influenced by technological change factors. Thus digitalization in the banking industry sector is essential. This research also provides recommendations for several parties, such as practitioners, academics, and regulators